Structure Effects on Organic Thin-Film Transistor Properties of Dinaphthyl Substituted Pentacene Derivatives - Ji-Hee Son; 강인남; 오세용; 박종욱 (Bulletin of the Korean Chemical Society, 2007)
Pentacene moiety has been widely studied in Organic Thin-Film Transistor (OTFT) device as a channel layer because of high carrier mobility. In this study, we have fabricated vertical type Organic Static Induction Transistors (SITs) using pentacene, 6,13-Dinaphthalen-1-ly-Pentacene (1-DNP, 3), and 6,13-Dinaphthalen-2-ly-Pentacene (2-DNP, 4). 1-DNP and 2-DNP have same naphtyl group with pentacene, but different linked position and spatial arrangement. We have checked the static characteristics of materials in vertical type SITs device. We found that pentacene has as on/off ratio of 14.56, 1-DNP and 2-DNP shows as on/off ratio of 36.58 and 6.61 at VDS=2V in SIT, respectively. KCI Citation Count: 4